Aqueous coloring coating composition and method for forming multilayer coating film

By developing an aqueous colored coating composition with a specific viscosity range and using a liquid discharge head to control the discharge during the coating process, the shortcomings of the coating composition in the prior art in terms of discharge stability and coating film sag resistance are solved, and higher coating performance is achieved.

CN119731280APending Publication Date: 2025-03-28KANSAI PAINT CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380059669.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-16
Filing Date
2023-04-07
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

There is room for improvement in the coating compositions in the prior art in terms of discharge stability and sag resistance of the coating film.

Method used

An aqueous colored coating composition is developed that has a specific viscosity range at a specific temperature and shear speed and contains an acrylic resin emulsion and a viscosity adjuster to improve discharge stability and sag resistance of the coating film.

Benefits of technology

When the aqueous colored coating composition is coated using the discharged liquid discharge head by changing the relative distance between the valve body and the discharge port, the discharge stability and the sag resistance and vividness of the formed coating film are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005270791520000211
    Figure BDA0005270791520000211
  • Figure BDA0005270791520000221
    Figure BDA0005270791520000221
  • Figure BDA0005270791520000271
    Figure BDA0005270791520000271
Patent Text Reader

Abstract

The purpose of the present invention is to provide an aqueous colored coating composition which, when coating is performed using a liquid discharge head that controls discharge by changing the relative distance between a valve body and a discharge port, has excellent discharge stability and forms a coating film having excellent sagging resistance and distinctness of image. A water-based colored coating composition for coating using a liquid discharge head that controls discharge by changing the relative distance between a valve body and a discharge port, the water-based colored coating composition having a viscosity (V1) of 20-100 mPa * s at a temperature of 23 DEG C and a shear rate of 1,000 sec <-1 > and a viscosity (V2) of 5,000-40,000 mPa * s at a temperature of 23 DEG C and a shear rate of 0.1 sec <-1 >, and a viscosity (V2) of 1,000 mPa.s to 2,000 mPa.s
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a water-based colored coating composition and a method for forming a multilayer coating film using the water-based colored coating composition. Background Art

[0002] A coating composition suitable for coating using a liquid discharge head that controls discharge by changing the relative distance between a valve body and a discharge port, and a method for forming a multilayer coating film using the coating composition have been studied.

[0003] For example, Patent Document 1 discloses a coating composition (claim 1), which is a coating composition for precision coating comprising a film-forming resin dispersed in an aqueous medium, a cross-linking agent capable of undergoing a cross-linking reaction with the film-forming resin, a rheology regulator, a colorant, and a swelling solvent capable of swelling the film-forming resin, wherein the solid content of the coating composition is less than 25 wt % based on the total weight of the coating composition.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: International Publication No. 2020 / 232011 Pamphlet Summary of the invention

[0007] Problem that the invention aims to solve

[0008] The coating composition of Patent Document 1 has room for improvement in terms of discharge stability of the coating composition, sagging of a coating film formed from the coating composition, and the like.

[0009] Therefore, an object of the present invention is to provide an aqueous colored coating composition which, when applied using a liquid discharge head that controls discharge by changing the relative distance between a valve body and a discharge port, has excellent discharge stability and a coating film formed that has excellent sag resistance and distinctness of image.

[0010] Solutions for solving problems

[0011] The inventors of the present application have discovered a water-based colored coating composition which is applied using a liquid discharge head that controls discharge by changing the relative distance between a valve body and a discharge port, and which has a temperature of 23° C. and a shear rate of 1,000 sec. -1 The viscosity (V1) is 20-100 mPa·s and the shear rate is 0.1 sec at a temperature of 23°C. -1 The viscosity (V2) is 5,000 to 40,000 mPa·s.

[0012] Effects of the Invention

[0013] The aqueous colored coating composition of the present invention is excellent in discharge stability and the formed coating film is excellent in sag resistance and distinctness of image when applied using a liquid discharge head that controls discharge by changing the relative distance between a valve body and a discharge port. DETAILED DESCRIPTION

[0014] Specifically, the present invention relates to the following embodiments.

[0015] [Implementation Method 1]

[0016] A water-based coloring coating composition is applied using a liquid discharge head that controls discharge by changing the relative distance between a valve body and a discharge port,

[0017] The aqueous colored coating composition has a temperature of 23°C and a shear rate of 1,000 sec. -1 The viscosity (V1) is 20-100 mPa·s and the shear rate is 0.1 sec at a temperature of 23°C. -1 The viscosity (V2) is 5,000 to 40,000 mPa·s.

[0018] The above-mentioned aqueous color coating composition has a predetermined viscosity (V1), so it is excellent in discharge stability. It should be noted that when the discharge stability of the aqueous color coating composition is poor, the thickness of the coating film formed by the aqueous color coating composition becomes uneven, and sometimes the smoothness and color reproducibility are poor, and sometimes the coating performance is poor.

[0019] Furthermore, since the water-based colored coating composition has a predetermined viscosity (V2), a coating film formed from the water-based colored coating composition is excellent in sag resistance and distinctness of image.

[0020] [Implementation Method 2]

[0021] The water-based colored coating composition according to Embodiment 1, wherein the solid content concentration of the water-based colored coating composition is within a range of 10 to 25% by mass.

[0022] Since the water-based colored coating composition has a predetermined solid content concentration, it is excellent in discharge stability, and a coating film formed from the water-based colored coating composition is excellent in distinctness of image.

[0023] [Implementation method 3]

[0024] The water-based colored coating composition according to embodiment 1 or 2, wherein the water-based colored coating composition has a tan δ (loss elastic modulus / storage elastic modulus) within a range of 0.25 to 0.80 at a temperature of 23°C.

[0025] Since the above aqueous colored coating composition has a specified tanδ, it has excellent discharge stability, and the distinctness of image of the coating film formed from the above aqueous colored coating composition is excellent.

[0026] [Embodiment 4]

[0027] The aqueous colored coating composition according to any one of Embodiments 1 to 3, wherein, under the condition of a temperature of 23°C, the shear rate is set to 0.1 sec -1 and after maintaining for 50 seconds, the viscosity (V3) of the above aqueous colored coating composition and the shear rate is changed to 1,000 sec -1 and after maintaining for 10 seconds, the viscosity (V4) of the above aqueous colored coating composition and the shear rate is changed to 0.1 sec -1 and after maintaining for 10 seconds, the viscosity (V5) of the above aqueous colored coating composition satisfies the following formulas (1) and (2):

[0028] 0.001 < V4 / V3 < 0.007 Formula (1)

[0029] 30 < V5 / V4 < 200 Formula (2).

[0030] Since the above aqueous colored coating composition satisfies Formula (1), the viscosity (V4) at the shear rate when discharging from the liquid discharge head is low, and it becomes easy to discharge the aqueous colored coating composition from the liquid discharge head in a restricted size, and the discharge stability is excellent. In addition, since the above aqueous colored coating composition satisfies Formula (2), the viscosity (V5) of the aqueous colored coating composition adhered to the object to be coated at the shear rate equivalent to sagging is high, and the sag resistance of the coating film formed from the above aqueous colored coating composition is excellent.

[0031] [Embodiment 5]

[0032] The aqueous colored coating composition according to any one of Embodiments 1 to 4, wherein the above aqueous colored coating composition contains an acrylic resin emulsion (A) and a viscosity modifier (B).

[0033] Since the above aqueous colored coating composition contains an acrylic resin emulsion (A) and a viscosity modifier (B), the sag resistance of the coating film formed from the above aqueous colored coating composition is excellent.

[0034] [Embodiment 6]

[0035] A method for forming a multilayer coating film, which has:

[0036] Step 1: using a liquid discharge head that controls discharge by changing the relative distance between a valve body and a discharge port, discharges the aqueous colored coating composition according to any one of Embodiments 1 to 5 adjacent to an object to be coated, thereby forming a colored coating film on the object to be coated;

[0037] Step 2: A clear coating composition is applied on the colored coating film to form a clear coating film.

[0038] In the above-mentioned method for forming a multilayer coating film, the discharge stability of the aqueous colored coating composition is excellent, and the coating film formed from the aqueous colored coating composition is excellent in sagging resistance.

[0039] [Implementation method 7]

[0040] The method for forming a multilayer coating film according to Embodiment 6, wherein the dried film thickness of the colored coating film is within a range of 1.0 to 15.0 μm.

[0041] In the above-mentioned method for forming a multilayer coating film, since the colored coating film has a predetermined dry film thickness, the multilayer coating film has excellent distinctness of image.

[0042] Hereinafter, the water-based colored coating composition of the present invention and the method for forming a multilayer coating film using the water-based colored coating composition (hereinafter referred to as the method for forming a multilayer coating film) will be described in detail.

[0043] [Water-based coloring coating composition]

[0044] The aqueous colored coating composition of the present invention is applied using a liquid discharge head that controls discharge by changing the relative distance between a valve body and a discharge port.

[0045] Examples of the liquid discharge head that controls discharge by changing the relative distance between the valve body and the discharge port include a head that discharges the aqueous coloring coating composition by shortening the relative distance between the valve body and the discharge port, and a head that discharges the aqueous coloring coating composition by increasing the relative distance between the valve body and the discharge port.

[0046] Examples of the liquid discharge head include on-demand type (eg, piezoelectric type, thermal type, valve type) and continuous type, among which on-demand type is preferred, and piezoelectric type is particularly preferred because of its excellent discharge performance for a high-viscosity aqueous colored coating composition.

[0047] Examples of the piezoelectric liquid discharge head include a piezoelectric jet dispenser and X JET (a type for high-viscosity liquids) manufactured by SSI JAPAN.

[0048] The aqueous colored coating composition has a temperature of 23°C and a shear rate of 1,000 sec. -1The viscosity (V1) is 20 to 100 mPa·s, preferably 30 to 60 mPa·s, and more preferably 45 to 60 mPa·s. Thus, the aqueous colored coating composition has excellent discharge stability from the liquid discharge head.

[0049] The above-mentioned aqueous colored coating composition has a temperature of 23°C and a shear rate of 0.1 sec -1 The viscosity (V2) is 5,000 to 40,000 mPa·s, preferably 11,000 to 35,000 mPa·s, and more preferably 25,000 to 30,000 mPa·s. Thus, the water-based color coating composition has excellent discharge stability, and the coating film formed from the water-based color coating composition has excellent sag resistance.

[0050] The water-based color coating composition has a tan δ (loss modulus / storage modulus) of preferably 0.25 to 0.80, more preferably 0.30 to 0.70, and further preferably 0.35 to 0.70 at a temperature of 23° C. Thus, the water-based color coating composition has excellent discharge stability, and a coating film formed from the water-based coating composition has excellent distinctness of image.

[0051] In addition, the measuring method of viscosity (V1), viscosity (V2) and tan δ is demonstrated in an Example.

[0052] The above aqueous coloring coating composition was heated to 23°C and the shear rate was set to 0.1 sec -1 Keep the viscosity (V3) after 50 seconds and change the shear rate to 1,000 sec. -1 Keep the viscosity (V4) after 10 seconds and change the shear rate to 0.1sec -1 And the viscosity (V5) after maintaining for 10 seconds, V4 / V3 is preferably greater than 0.001, more preferably greater than 0.002, further preferably greater than 0.003, and preferably less than 0.007, more preferably less than 0.006, and further preferably less than 0.005. Thus, the viscosity (V4) at the shear rate when discharged from the liquid discharge head is low, it becomes easy to discharge the above-mentioned aqueous color coating composition from the liquid discharge head in a limited size, and the discharge stability of the above-mentioned aqueous color coating composition is excellent.

[0053] In addition, V5 / V4 is preferably greater than 30, more preferably greater than 50, and further preferably greater than 60, and is preferably less than 200, more preferably less than 180, and further preferably less than 160. As a result, the viscosity (V5) of the aqueous colored coating composition attached to the coated object at a shear rate corresponding to sagging is high, and the coating film formed from the aqueous colored coating composition is excellent in sagging resistance.

[0054] In addition, the measuring method of viscosity (V3), viscosity (V4) and viscosity (V5) is demonstrated in Example.

[0055] The water-based color coating composition preferably has a solid content concentration of 10 to 25% by mass, more preferably 10 to 20% by mass, and further preferably 10 to 16% by mass. Thus, the water-based color coating composition has excellent discharge stability and a coating film formed from the water-based coating composition has excellent distinctness of image.

[0056] In this specification, the solid content concentration can be calculated as follows: a measurement object (e.g., a water-based coloring coating composition) is measured in a heat-resistant container such as an aluminum foil cup, the measurement object is spread on the bottom of the container, and then dried at 110° C. for 1 hour, and the mass of the component in the measurement object remaining after drying is weighed, and the ratio of the mass of the component in the measurement object remaining after drying to the total mass of the measurement object before drying is calculated.

[0057] The aqueous colored coating composition is not particularly limited as long as it has the above-mentioned viscosity, and may contain a resin such as an acrylic resin, a polyester resin, an alkyd resin, a polyurethane resin, an epoxy resin, a silicone resin, or any combination thereof.

[0058] The resin may be an emulsion, for example, may include: acrylic resin emulsion, polyester resin emulsion, alkyd resin emulsion, polyurethane resin emulsion, epoxy resin emulsion, silicone resin emulsion, any combination thereof, etc.

[0059] The resin preferably includes an acrylic resin emulsion (acrylic resin emulsion (A)).

[0060] The acrylic resin emulsion (A) is obtained by emulsifying and dispersing an acrylic resin in an aqueous medium. For example, an emulsion produced by emulsion polymerization of a polymerizable unsaturated monomer mixture can be mentioned.

[0061] As the acrylic resin emulsion (A), a core-shell type emulsion is particularly preferred, wherein the core-shell type emulsion comprises a core portion formed by a copolymer (I) and a shell portion formed by a copolymer (II). Furthermore, from the perspective of improving the appearance and water resistance of the resulting coating film, it is preferred that the copolymer (I) is obtained by copolymerizing a polymerizable unsaturated monomer (a1) having two or more polymerizable unsaturated groups in one molecule and a polymerizable unsaturated monomer (a2) other than the polymerizable unsaturated monomer (a1), and the copolymer (II) is obtained by copolymerizing a plurality of polymerizable unsaturated monomers (a3).

[0062] Examples of the polymerizable unsaturated monomer (a1) include ethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, allyl (meth)acrylate, divinylbenzene, trimethylolpropane triacrylate, methylenebis(meth)acrylamide, ethylenebis(meth)acrylamide, and combinations thereof.

[0063] In addition, in this specification, "(meth)acrylate" means acrylate and / or methacrylate.

[0064] The polymerizable unsaturated monomer (a2) other than the polymerizable unsaturated monomer (a1) (hereinafter sometimes referred to as "polymerizable unsaturated monomer (a2)") is a monomer copolymerizable with the polymerizable unsaturated monomer (a1) and having one polymerizable unsaturated group in one molecule. It may include a compound having a polymerizable unsaturated group such as a vinyl group or a (meth)acryloyl group.

[0065] Specific examples of the polymerizable unsaturated monomer (a2) include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, n-hexyl (meth)acrylate, n-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, tridecyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, isostearyl acrylate (trade name, manufactured by Osaka Organic Chemical Industry Co., Ltd.), cyclohexyl (meth)acrylate, methylcyclohexyl (meth)acrylate, tert-butylcyclohexyl (meth)acrylate, Alkyl or cycloalkyl (meth)acrylates such as cyclododecyl (meth)acrylate; polymerizable unsaturated monomers having an isobornyl group such as isobornyl (meth)acrylate; polymerizable unsaturated monomers having an adamantyl group such as adamantyl (meth)acrylate; vinyl aromatic compounds such as styrene, α-methylstyrene, and vinyltoluene; polymerizable unsaturated monomers having an alkoxysilyl group such as vinyltrimethoxysilane, vinyltriethoxysilane, vinyltri(2-methoxyethoxy)silane, γ-(meth)acryloxypropyltrimethoxysilane, and γ-(meth)acryloxypropyltriethoxysilane; (meth)acrylates such as perfluorobutylethyl (meth)acrylate and perfluorooctylethyl (meth)acrylate Fluoroalkyl esters; polymerizable unsaturated monomers having fluoroalkyl groups such as fluoroolefins; monomers having photopolymerizable functional groups such as maleimide groups; vinyl compounds such as N-vinyl pyrrolidone, ethylene, butadiene, chloroprene, vinyl propionate, and vinyl acetate; polymerizable unsaturated monomers containing carboxyl groups such as (meth)acrylic acid, maleic acid, crotonic acid, and β-carboxyethyl acrylate; nitrogen-containing polymerizable unsaturated monomers such as (meth)acrylonitrile, (meth)acrylamide, N,N-dimethylaminoethyl (meth)acrylate, N,N-dimethylaminopropyl (meth)acrylamide, and adducts of glycidyl (meth)acrylate and amines; 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and (meth)acrylonitrile. Monoesters of (meth)acrylic acid and diols having 2 to 8 carbon atoms, such as 3-hydroxypropyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate; ε-caprolactone-modified monoesters of (meth)acrylic acid and diols having 2 to 8 carbon atoms, N-hydroxymethyl (meth)acrylamide, allyl alcohol, (meth)acrylates having a polyoxyethylene chain with a hydroxyl group at the molecular end, and other hydroxyl-containing polymerizable unsaturated monomers; glycidyl (meth)acrylate, β-methylglycidyl (meth)acrylate, 3,4-epoxycyclohexylmethyl (meth)acrylate, 3,4-epoxycyclohexylethyl (meth)acrylate, 3,4-epoxycyclohexylpropyl (meth)acrylate, allyl glycidyl ether, and other epoxy-containing polymerizable unsaturated monomers;(Meth)acrylates having a polyoxyethylene chain with an alkoxy group at the molecular end; polymerizable unsaturated monomers containing a sulfonic acid group, such as 2-acrylamide-2-methylpropanesulfonic acid, allylsulfonic acid, sodium styrenesulfonate, methacrylic acid sulfoethyl ester and its sodium salt or ammonium salt; polymerizable unsaturated monomers containing a phosphoric acid group, such as 2-acryloyloxyethyl acid phosphate, 2-methacryloyloxyethyl acid phosphate, 2-acryloyloxypropyl acid phosphate, 2-methacryloyloxypropyl acid phosphate; 2-hydroxy-4-(3- Monomers having ultraviolet absorbing functional groups such as 2-(2-methacryloyloxy)benzophenone, 2-hydroxy-4-(3-acryloyloxy-2-hydroxypropoxy)benzophenone, 2,2'-dihydroxy-4-(3-methacryloyloxy-2-hydroxypropoxy)benzophenone, 2,2'-dihydroxy-4-(3-acryloyloxy-2-hydroxypropoxy)benzophenone, and 2-(2'-hydroxy-5'-methacryloyloxyethylphenyl)-2H-benzotriazole; 4-(methacryloyloxy)benzophenone, 2-hydroxy-4-(3-methacryloyloxy-2-hydroxypropoxy)benzophenone, 2,2'-dihydroxy-4-(3-acryloyloxy-2-hydroxypropoxy)benzophenone, and 2-(2'-hydroxy-5'-methacryloyloxyethylphenyl)-2H-benzotriazole; 1,2,2,6,6-pentamethylpiperidine, 4-(meth)acryloyloxy-2,2,6,6-tetramethylpiperidine, 4-cyano-4-(meth)acryloylamino-2,2,6,6-tetramethylpiperidine, 1-(meth)acryloyl-4-(meth)acryloylamino-2,2,6,6-tetramethylpiperidine, 1-(meth)acryloyl-4-cyano-4-(meth)acryloylamino-2,2,6,6-tetramethylpiperidine, 4-crotonyloxy-2,2,6 ,6-tetramethylpiperidine, 4-crotonylamino-2,2,6,6-tetramethylpiperidine, 1-crotonyl-4-crotonyloxy-2,2,6,6-tetramethylpiperidine and other ultraviolet stable monomers; acrolein, diacetone acrylamide, diacetone methacrylamide, acetoacetoxyethyl methacrylate, formyl styrene, vinyl alkyl ketones having 4 to 7 carbon atoms (such as vinyl methyl ketone, vinyl ethyl ketone, vinyl butyl ketone) and other carbonyl-containing monomer compounds and their combinations. ;

[0066] When producing the copolymer (I), from the viewpoints of improving the stability during production, the water resistance and weather resistance of the obtained coating film, etc., the content of the polymerizable unsaturated monomer (a1) is preferably in the range of 0.1 to 20% by mass, more preferably 0.2 to 10% by mass, and further preferably 0.7 to 4% by mass, based on the total mass of the polymerizable unsaturated monomer (a1) and the polymerizable unsaturated monomer (a2). Furthermore, the content of the polymerizable unsaturated monomer (a2) is preferably in the range of 80 to 99.9% by mass, more preferably 90 to 99.8% by mass, and further preferably 96 to 99.3% by mass, based on the total mass of the polymerizable unsaturated monomer (a1) and the polymerizable unsaturated monomer (a2).

[0067] As the multiple polymerizable unsaturated monomers (a3) ​​forming the shell part of the copolymer (II), the monomers listed in the polymerizable unsaturated monomers (a2) can be appropriately used. From the viewpoint of being able to ensure the stability of the obtained core-shell emulsion in an aqueous medium, the polymerizable unsaturated monomers (a3) ​​in the shell part of the copolymer (II) preferably include carboxyl-containing monomers. As the above-mentioned carboxyl-containing monomers, acrylic acid and / or methacrylic acid are particularly preferred. From the viewpoint of being able to ensure the stability of the emulsion resin in an aqueous medium and the water resistance of the obtained coating film, it is suitable to improve the storage stability and the water resistance of the obtained coating film that the amount of the carboxyl-containing monomer is preferably 1 to 40% by mass, more preferably 6 to 25% by mass, and further preferably in the range of 7 to 19% by mass, based on the total mass of the multiple polymerizable unsaturated monomers (a3).

[0068] In addition, as the plurality of polymerizable unsaturated monomers (a3) ​​forming the shell part of the copolymer (II), from the viewpoint of being able to ensure the stability of the obtained emulsion resin in an aqueous medium, in order to improve the stability of the emulsion resin in an aqueous medium, it is suitable that at least a part of the component contains the above-mentioned hydroxyl-containing monomer. As hydroxyl-containing monomers, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate are particularly preferred. From the viewpoints of the stability of the emulsion resin in an aqueous medium, the water resistance of the obtained coating film, etc., in terms of improving the storage stability and the water resistance of the obtained coating film, it is suitable that the amount of the hydroxyl-containing monomer is usually 1 to 40% by mass, preferably 3 to 25% by mass, and more preferably 4 to 20% by mass based on the total mass of the plurality of polymerizable unsaturated monomers (a3).

[0069] The core-shell emulsion can be obtained, for example, by emulsion polymerization of a monomer mixture (1) containing a polymerizable unsaturated monomer (a1) and a polymerizable unsaturated monomer (a2) in the above ratio to generate a copolymer (I), followed by adding a monomer mixture (2) containing a plurality of polymerizable unsaturated monomers (a3), and further emulsion polymerization to obtain the core-shell emulsion. The emulsion polymerization of the monomer mixture (1) can be carried out by a method known per se, for example, using a polymerization initiator in the presence of an emulsifier. The monomer mixture (2) can contain components such as a polymerization initiator, a chain transfer agent, a reducing agent, and an emulsifier as required.

[0070] The core-shell emulsion is a core / shell emulsion, which uses a copolymer (I) formed from a monomer mixture (1) containing a polymerizable unsaturated monomer (a1) and a polymerizable unsaturated monomer (a2) as a core, and a copolymer (II) formed from a monomer mixture (2) containing a plurality of polymerizable unsaturated monomers (a3) ​​as a shell. Regarding the ratio of the copolymer (I) to the copolymer (II) in the core-shell emulsion, from the viewpoint of the sag resistance of the obtained coating film, the solid content mass ratio of the copolymer (I) / copolymer (II) is usually 5 / 95 to 95 / 5, particularly preferably 30 / 70 to 92 / 8, and more preferably 40 / 60 to 90 / 10.

[0071] As the acrylic resin emulsion (A), a single-layer type acrylic resin emulsion obtained by performing one-step emulsion polymerization can also be used.

[0072] The acrylic resin emulsion (A) obtained as described above preferably has a resin acid value in the range of 5 to 90 mgKOH / g, more preferably 8 to 60 mgKOH / g, and further preferably 10 to 50 mgKOH / g from the viewpoints of storage stability and water resistance of the obtained coating film. In addition, the acrylic resin emulsion (A) preferably has a resin hydroxyl value in the range of 1 to 100 mgKOH / g, more preferably 2 to 90 mgKOH / g, and further preferably 5 to 80 mgKOH / g from the viewpoints of water resistance of the obtained coating film.

[0073] When the aqueous color coating composition of the present invention contains the acrylic resin emulsion, the content of the acrylic resin emulsion (A) is preferably in the range of 15 to 60% by mass, more preferably in the range of 20 to 55% by mass, and further preferably in the range of 25 to 45% by mass, based on the resin solid content in the aqueous color coating composition.

[0074] The above-mentioned water-based coloring coating composition may further contain a curing agent. As the above-mentioned curing agent, for example, amino resins, polyisocyanate compounds, blocked polyisocyanate compounds, epoxy-containing compounds, carboxyl-containing compounds, carbodiimide-containing compounds, hydrazide-containing compounds, and semicarbazide-containing compounds can be listed. Among these compounds, amino resins, polyisocyanate compounds, blocked polyisocyanate compounds, and carbodiimide-containing compounds that can react with hydroxyl groups are preferred.

[0075] The above-mentioned aqueous coloring coating composition preferably further contains a viscosity adjuster (B). Examples of the viscosity adjuster (B) include polyacrylic acid-based viscosity adjusters, silica-based fine powders, mineral-based viscosity adjusters, barium sulfate micronized powders, polyamide-based viscosity adjusters, organic resin microparticle viscosity adjusters, diurea-based viscosity adjusters, urethane-associated viscosity adjusters, and cellulose-based viscosity adjusters, and polyacrylic acid-based viscosity adjusters are preferred.

[0076] When the aqueous colored coating composition of the present invention contains a viscosity adjuster (B), the content of the viscosity adjuster (B) is preferably in the range of 0.1 to 10% by mass, more preferably in the range of 0.5 to 8% by mass, and further preferably in the range of 1.0 to 6.0% by mass, based on the resin solid content in the aqueous colored coating composition.

[0077] The above-mentioned water-based colored coating composition may contain various coating additives such as coloring pigments, bright pigments, dyes, thickeners, curing catalysts, ultraviolet absorbers, light stabilizers, defoamers, plasticizers, surface conditioners, anti-settling agents, etc. as needed.

[0078] [Method for forming a multilayer coating film]

[0079] The method for forming a multilayer coating film of the present invention includes the following steps.

[0080] Step 1: using a liquid discharge head that controls discharge by changing the relative distance between a valve body and a discharge port, a predetermined aqueous colored coating composition is discharged adjacent to an object to be coated, thereby forming a colored coating film on the object to be coated;

[0081] Step 2: A clear coating composition is applied on the colored coating film to form a clear coating film.

[0082] The liquid discharge head that controls discharge by changing the relative distance between the valve body and the discharge port is described in the section of [aqueous colored coating composition].

[0083] The dry film thickness of the colored coating film formed from the aqueous colored coating composition may vary depending on the application of the coated object, etc., and is not particularly limited. From the viewpoint of image distinctness of the multilayer coating film, it is preferably 1.0 to 15.0 μm, more preferably 3.0 to 15.0 μm, and even more preferably 5.0 to 15.0 μm.

[0084] Examples of the objects to be coated include outer panels of automobile bodies such as passenger cars, trucks, motorcycles, and buses; automobile parts; and outer panels of household electrical appliances such as mobile phones and audio equipment. Outer panels of automobile bodies and automobile parts are preferred.

[0085] The material of the above-mentioned coated object is not particularly limited, and examples thereof include metal materials such as iron, aluminum, brass, copper, tinplate, stainless steel, galvanized steel, and zinc alloy (Zn-Al, Zn-Ni, Zn-Fe, etc.) steel; resins such as polyethylene resin, polypropylene resin, acrylonitrile-butadiene-styrene (ABS) resin, polyamide resin, acrylic resin, vinylidene chloride resin, polycarbonate resin, polyurethane resin, epoxy resin, and plastic materials such as various fiber reinforced plastics (FRP); inorganic materials such as glass, cement, and concrete; wood; fiber materials such as paper and cloth, and the like.

[0086] The surface of the object to be coated may be a surface treated by phosphate treatment, chromate treatment, composite oxide treatment or the like on the metal surface of automobile body panels, automobile parts, household electrical appliances, or metal substrates such as steel sheets constituting them.

[0087] On the object which may or may not be subjected to surface treatment, a coating film may be further formed. For example, a surface treatment may be applied to the object to be coated as a substrate as needed, and a primer coating film may be formed thereon, or a mid-coat coating film may be formed on the primer coating film. The primer coating film and the mid-coat coating film may be formed using known primer coatings and mid-coat coatings commonly used in the coating of automobile bodies, for example, when the object to be coated is an automobile body.

[0088] The distance between the discharge port and the object to be coated may be any distance generally used in the liquid discharge head and is not particularly limited, but is preferably 0.1 to 50.0 mm, more preferably 0.5 to 30 mm, and further preferably 1.0 to 10.0 mm.

[0089] In the device including the above-mentioned liquid discharge head, from the viewpoint of discharge stability and the difficulty in causing unevenness in the formed coating film, the frequency when the aqueous colored coating composition is discharged from the valve body is preferably in the range of 10 to 10,000 Hz, more preferably in the range of 30 to 5,000 Hz, and further preferably in the range of 50 to 3,000 Hz.

[0090] In the device having the above liquid discharge head, the supply pressure of the aqueous colored coating composition supplied by the liquid discharge head is preferably in the range of 0.001 to 10 MPa, more preferably in the range of 0.005 to 5.0 MPa, and further preferably in the range of 0.01 to 1.0 MPa from the viewpoint of supply stability.

[0091] In the device equipped with the above-mentioned liquid discharge head, from the viewpoint of discharge stability and difficulty in producing unevenness in the formed coating film, the scanning speed of the liquid discharge head is preferably in the range of 10 to 1,500 mm / s, more preferably in the range of 50 to 1,000 mm / s, and further preferably in the range of 100 to 800 mm / s.

[0092] In the device having the above-mentioned liquid discharge head, from the viewpoint of coating efficiency, the pitch during scanning of the liquid discharge head is preferably in the range of 0.001 to 1.0 mm, more preferably in the range of 0.005 to 1.0 mm, and further preferably in the range of 0.01 to 1.0 mm.

[0093] Examples of the above-mentioned clear coating composition include curable clear coating compositions (e.g., thermosetting clear coating compositions, photocurable clear coating compositions) and non-curable clear coating compositions. Examples of the above-mentioned thermosetting clear coating composition include organic solvent-based thermosetting coating compositions, water-based thermosetting coating compositions, powder thermosetting coating compositions, etc., which contain a base resin having a crosslinkable functional group and a curing agent.

[0094] Examples of the crosslinkable functional group of the base resin include carboxyl, hydroxyl, epoxy, and silanol groups. Examples of the type of base resin include acrylic resins, polyester resins, alkyd resins, polyurethane resins, epoxy resins, and fluororesins. Examples of curing agents include polyisocyanate compounds, blocked polyisocyanate compounds, melamine resins, urea resins, carboxyl-containing compounds, carboxyl-containing resins, epoxy-containing resins, and epoxy-containing compounds.

[0095] As the combination of base resin / curing agent of the above-mentioned clear coating composition, preferred are hydroxyl-containing resin / polyisocyanate compound, carboxyl-containing resin / epoxy-containing resin, hydroxyl-containing resin / blocked polyisocyanate compound, hydroxyl-containing resin / melamine resin, and more preferred is hydroxyl-containing resin / polyisocyanate compound.

[0096] The clear coating composition may be a one-component coating or a multi-component coating such as a two-component urethane resin coating.

[0097] In addition, the above-mentioned clear coating composition may contain coloring pigments, bright pigments, dyes, etc. as needed to the extent that transparency is not impaired, and may further contain extender pigments, ultraviolet absorbers, light stabilizers, defoamers, thickeners, rust inhibitors, surface conditioners, etc.

[0098] The coating method of the above-mentioned clear coating composition is not particularly limited, and a wet coating film can be formed by, for example, air spraying, airless spraying, rotary atomization coating, curtain coating and other coating methods. In these coating methods, electrostatic application can be performed as needed. Among them, air spray coating or rotary atomization coating is particularly preferred. The coating amount of the clear coating composition is usually set to reach 10 to 70 μm, preferably 20 to 50 μm in terms of cured film thickness.

[0099] Example

[0100] Hereinafter, the present invention will be described in more detail by enumerating manufacturing examples, embodiments and comparative examples. However, the present invention is not limited thereto. In each example, unless otherwise specified, "parts" and "%" are based on a mass basis. In addition, the film thickness of the coating film is based on the cured coating film.

[0101] [Production of acrylic resin emulsion (A)]

[0102] [Production Example 1]

[0103] 130 parts of deionized water and 0.52 parts of "Aqualon KH-10" (trade name, manufactured by Daiichi Kogyo Seiyaku Co., Ltd., emulsifier, effective ingredient 97%) were placed in a reaction container equipped with a thermometer, a thermostat, a stirrer, a reflux cooler, a nitrogen inlet pipe and a dropping device, stirred and mixed in a nitrogen stream, and the temperature was raised to 80°C. Next, 1% of the total amount of the following monomer emulsion (1) and 5.3 parts of a 6% ammonium persulfate aqueous solution were introduced into the reaction container, and kept at 80°C for 15 minutes. Then, the remaining monomer emulsion (1) was added dropwise to the reaction container maintained at the same temperature over 3 hours, and after the completion of the dropping, it was aged for 1 hour. Then, the following monomer emulsion (2) was added dropwise over 1 hour, and after aging for 1 hour, 40 parts of a 5% dimethylethanolamine aqueous solution was slowly added to the reaction container while cooling to 30°C, and the mixture was discharged while filtering with a 100-mesh nylon cloth to obtain an acrylic resin emulsion (A1) with a solid content concentration of 30%. The acid value of the obtained acrylic resin emulsion (A1) was 33 mgKOH / g and the hydroxyl value was 25 mgKOH / g.

[0104] Monomer emulsion (1): 42 parts of deionized water, 0.72 parts of "Aqualon KH-10", 2.1 parts of methylenebisacrylamide, 2.8 parts of styrene, 16.1 parts of methyl methacrylate, 28 parts of ethyl acrylate and 21 parts of n-butyl acrylate were mixed and stirred to obtain a monomer emulsion (1).

[0105] Monomer emulsion (2): 18 parts of deionized water, 0.31 parts of "Aqualon KH-10", 0.03 parts of ammonium persulfate, 5.1 parts of methacrylic acid, 5.1 parts of 2-hydroxyethyl acrylate, 3 parts of styrene, 6 parts of methyl methacrylate, 1.8 parts of ethyl acrylate and 9 parts of n-butyl acrylate were mixed and stirred to obtain a monomer emulsion (2).

[0106] [Production Example 2]

[0107] 130 parts of deionized water and 0.52 parts of "Aqualon KH-10" (trade name, manufactured by Daiichi Kogyo Seiyaku Co., Ltd., emulsifier, effective ingredient 97%) were placed in a reaction container equipped with a thermometer, a thermostat, a stirrer, a reflux cooler, a nitrogen inlet pipe and a dropping device, stirred and mixed in a nitrogen stream, and heated to 80°C. Next, 1% of the total amount of the following monomer emulsion (3) and 5.3 parts of a 6% aqueous solution of ammonium persulfate were introduced into the reaction container, and kept at 80°C for 15 minutes. Then, the remaining monomer emulsion (3) was added dropwise to the reaction container maintained at the same temperature over 3 hours, and after the completion of the addition, it was aged for 1 hour. Then, the following monomer emulsion (4) was added dropwise over 1 hour, and after aging for 1 hour, 40 parts of a 5% aqueous solution of dimethylethanolamine was slowly added to the reaction container while cooling to 30°C, and the mixture was discharged while filtering with a 100-mesh nylon cloth, thereby obtaining an acrylic resin emulsion (A2) having a solid content concentration of 30%. The obtained acrylic resin emulsion (A2) had an acid value of 13 mgKOH / g and a hydroxyl value of 65 mgKOH / g.

[0108] Monomer emulsion (3): 46.2 parts of deionized water, 0.79 parts of "Aqualon KH-10", 7.7 parts of styrene, 16.94 parts of methyl methacrylate, 7.7 parts of n-butyl acrylate, 30.8 parts of n-butyl methacrylate, 11.55 parts of 2-hydroxyethyl methacrylate and 2.31 parts of ethylene glycol dimethacrylate were mixed and stirred to obtain monomer emulsion (3).

[0109] Monomer emulsion (4): 13.8 parts of deionized water, 0.24 parts of "Aqualon KH-10", 0.03 parts of ammonium persulfate, 2.3 parts of styrene, 6.9 parts of methyl methacrylate, 4.6 parts of ethyl acrylate, 3.68 parts of n-butyl acrylate, 3.45 parts of 2-hydroxyethyl methacrylate and 2.07 parts of methacrylic acid were mixed and stirred to obtain monomer emulsion (4).

[0110] [Production of Hydroxyl-Containing Acrylic Resin (C)]

[0111] [Production Example 3]

[0112] 35 parts of propylene glycol monopropyl ether were placed in a reaction vessel equipped with a thermometer, a thermostat, a stirrer, a reflux cooler, a nitrogen inlet pipe and a dropping device. After the temperature was raised to 85°C, a mixture of 30 parts of methyl methacrylate, 20 parts of 2-ethylhexyl acrylate, 29 parts of n-butyl acrylate, 15 parts of 2-hydroxyethyl acrylate, 6 parts of acrylic acid, 15 parts of propylene glycol monopropyl ether and 2.3 parts of 2,2'-azobis(2,4-dimethylvaleronitrile) was added dropwise over 4 hours, and the mixture was aged for 1 hour after the addition was completed. Then, a mixture of 10 parts of propylene glycol monopropyl ether and 1 part of 2,2'-azobis(2,4-dimethylvaleronitrile) was further added dropwise over 1 hour, and the mixture was aged for 1 hour after the addition was completed. 7.4 parts of diethanolamine and 13 parts of propylene glycol monopropyl ether were further added to obtain a hydroxyl-containing acrylic resin (C1) solution having a solid content concentration of 55%. The obtained hydroxyl-containing acrylic resin (C1) had an acid value of 47 mgKOH / g, a hydroxyl value of 72 mgKOH / g, and a weight average molecular weight of 58,000.

[0113] [Production of polyester resin (D)]

[0114] [Production Example 4]

[0115] 118 parts of 1,6-hexanediol and 102 parts of adipic acid were mixed in a reaction device equipped with a thermometer, a stirrer, a heating device and a distillation tower, and a small amount of xylene for reflux was further added, and the mixture was slowly heated to 250°C and maintained at the temperature for 5 hours to carry out an esterification reaction while dehydrating, thereby obtaining a polyester resin. 102.5 parts of ethylene glycol monobutyl ether and 2.5 parts of orthophosphoric acid were added to 100 parts of the polyester resin, and the mixture was maintained at 100°C for 3 hours to obtain a polyester resin (D1) solution having a solid content concentration of 50%. The number average molecular weight of the polyester resin (D1) was 4,000.

[0116] [Manufacturing of Pigment Dispersion]

[0117] [Production Example 5]

[0118] 9.1 parts (5 parts solid content) of the hydroxyl-containing acrylic resin (C1) solution obtained in Production Example 3, 4 parts of "Carbon MA-100" (trade name, manufactured by Mitsubishi Chemical Corporation, carbon black) and 50 parts of deionized water were added to a container equipped with a stirring device, and uniformly mixed to form a mixed solution. 2-ethyl-1-hexanol was added to the mixed solution to adjust the pH to 7.5. Next, the pH-adjusted mixed solution was placed in a wide-mouthed glass bottle, and a granular material with a diameter of about 1.5 mm was added as a dispersion medium. The mixture was mixed with glass beads and sealed, and dispersed for 4 hours using a paint shaker to obtain a pigment dispersion (P-1).

[0119] [Production Example 6]

[0120] 9.1 parts (5 parts solid content) of the hydroxyl-containing acrylic resin (C1) solution obtained in Production Example 3, 7 parts of "Cyanine Blue-G-314" (trade name, manufactured by Sanyo Pigment Co., Ltd., phthalocyanine blue pigment) and 50 parts of deionized water were added to a container equipped with a stirring device, and uniformly mixed to form a mixed solution. 2-ethyl-1-hexanol was added to the mixed solution and the pH was adjusted to 7.5. Next, the pH-adjusted mixed solution was placed in a wide-mouthed glass bottle, and a granular material with a diameter of about 1.5 was added as a dispersion medium. The mixture was mixed with glass beads and sealed, and dispersed for 4 hours using a paint shaker to obtain a pigment dispersion (P-2).

[0121] [Production Example 7]

[0122] 9.1 parts (5 parts solid content) of the hydroxyl-containing acrylic resin (C1) solution obtained in Production Example 3, 10 parts of "PERRIND MAROON 179229-6440" (trade name, manufactured by Sun Chemical Co., Ltd., organic perylene pigment) and 50 parts of deionized water were added to a container equipped with a stirring device, and uniformly mixed to form a mixed solution. 2-ethyl-1-hexanol was added to the mixed solution, and the pH was adjusted to 7.5. Next, the pH-adjusted mixed solution was placed in a wide-mouthed glass bottle, and a granular material with a diameter of about 1.5 was added as a dispersion medium. The mixture was mixed with glass beads and sealed, and dispersed for 4 hours using a paint shaker to obtain a pigment dispersion (P-3).

[0123] [Production Example 8]

[0124] 9.1 parts (5 parts solid content) of the hydroxyl-containing acrylic resin (C1) solution obtained in Production Example 3, 10 parts of "YELLOW 2GLMA" (trade name, manufactured by Dominion Colour Corporation, bismuth vanadate yellow pigment) and 50 parts of deionized water were added to a container equipped with a stirring device, and uniformly mixed to form a mixed solution. 2-ethyl-1-hexanol was added to the mixed solution, and the pH was adjusted to 7.5. Next, the pH-adjusted mixed solution was placed in a wide-mouthed glass bottle, and a dispersion medium having a diameter of about 1.5 was added. The mixture was mixed with glass beads and sealed, and dispersed for 4 hours using a paint shaker to obtain a pigment dispersion (P-4).

[0125] [Preparation of water-based coloring coating composition]

[0126] [Example 1]

[0127] In a stirring mixing container, 63.1 parts (9 parts solid content) of the pigment dispersion (P-1) obtained in Preparation Example 5, 116.7 parts (35.0 parts solid content) of the acrylic resin emulsion (A1) obtained in Preparation Example 1, 16.1 parts (4.5 parts solid content) of "Primal ASE-60" (trade name, manufactured by Rohm and Haas, polyacrylic acid thickener, 28% solid content), 30 parts (15 parts solid content) of the hydroxyl-containing polyester resin (D1) solution obtained in Preparation Example 4, 42.9 parts (15 parts solid content) of "U-COAT UX-8100" (trade name, manufactured by Sanyo Chemical Industries, Ltd., urethane emulsion, solid content concentration 35%), and 30 parts (30 parts solid content) of "Cymel 350" (trade name, manufactured by Mitsui Cytec Co., Ltd., methyl etherified melamine resin, weight average molecular weight 550, solid content 100%) and 1.1 parts (solid content 1 part) of "TINUVIN 384-2" (trade name, manufactured by BASF, benzotriazole-based ultraviolet absorber, solid content concentration 95%), 2-(dimethylamino)ethanol and deionized water were added to obtain an aqueous colored coating composition No. 1 having a pH of 8.0 and a coating solid content concentration of 15%.

[0128] [Examples 2 to 20 and Comparative Examples 1 to 4]

[0129] In Example 1, except having made the formulation composition into the composition shown in the following Table 1, it carried out similarly to Example 1, and obtained the water-based coloring coating composition No. 2 - No. 24.

[0130] It should be noted that the numerical values ​​shown in Table 1 refer to the solid content.

[0131] [Determination of coating properties]

[0132] The coating properties of the water-based colored coating compositions No. 1 to No. 24 obtained in Examples 1 to 20 and Comparative Examples 1 to 4 were measured by the following methods. The evaluation results are also shown in Table 1.

[0133] [Viscosity (V1) and Viscosity (V2)]

[0134] At 23°C, the shear rate was increased from 0.0001 sec -1 Change to 10,000sec -1 The viscometer was measured using a cone-plate viscometer "HAAKE RheoStress RS150" (trade name, manufactured by HAAKE, 35 mm diameter, 2° inclined cone-plate) at a temperature of 23°C and a shear rate of 1,000 sec. -1 The viscosity (V1) at 23°C and shear rate of 0.1 sec-1 The viscosity (V2) below.

[0135] [tanδ]

[0136] Tan δ (loss modulus / storage modulus) at 23°C was measured using "HAAKE RheoStress RS150" (trade name, manufactured by HAAKE, 35 mm diameter, 2° inclined cone plate) with a shear stress of 1.0 Pa and a frequency of 0.1 Hz.

[0137] [Viscosity (V3), Viscosity (V4) and Viscosity (V5)]

[0138] First, set the shear rate to 0.1 sec. -1 , measure the viscosity (V3) after holding for 50 seconds. Then, change the shear rate to 1000 sec. -1 , measure the viscosity (V4) after holding for 10 seconds. Then, change the shear rate to 0.1 sec -1 The viscosity (V5) after holding for 10 seconds was measured. All measurements were performed at a temperature of 23°C using "HAAKE RheoStress RS150" (trade name, manufactured by HAAKE, 35 mm in diameter, cone plate inclined at 2°).

[0139] [Discharge stability test and sagging resistance test]

[0140] The water-based colored coating compositions No. 1 to No. 24 obtained in Examples 1 to 20 and Comparative Examples 1 to 4 were subjected to a discharge stability test and a sagging resistance test.

[0141] [Discharge stability test]

[0142] The water-based coloring coating compositions No. 1 to No. 24 were filled in "X JET" (trade name, manufactured by SSI JAPAN, high viscosity micro-piezoelectric jet dispenser, discharge port diameter 100 μm). Then, under the conditions of frequency 350 Hz, supply pressure 0.03 MPa, speed 230 mm / s, and a distance of 10 mm between the discharge port and the coated object, the water-based coloring coating compositions No. 1 to No. 24 were applied to the coated object in a linear shape (length 10 cm), and the deformation of the linear object was observed and evaluated according to the following criteria. ◎ and ○ are qualified. The evaluation results are shown in Table 2.

[0143] ◎: The linear object is not deformed.

[0144] ○: The linear object is partially deformed, but there is no problem in practical use.

[0145] △: The entire linear object is deformed, which is problematic for practical use.

[0146] ×: Linear material cannot be formed.

[0147] [Anti-sagging test]

[0148] [Preparation of coated material for sag resistance test]

[0149] On a cold-rolled steel sheet with a size of 11 cm×45 cm and subjected to zinc phosphate chemical conversion treatment, "ELECRON9400 HB" (trade name: manufactured by Kansai Paint Co., Ltd., which is obtained by using a blocked polyisocyanate compound as a curing agent in an amine-modified epoxy resin-based cationic resin) was electro-deposited to a dry film thickness of 20 μm, and heated at 170°C for 30 minutes to cure it, thereby obtaining an electro-deposited coated steel sheet. Next, 21 punched holes with a diameter of 5 mm were provided in a row at intervals of 2 cm in a portion 3 cm from the end on the long dimension side of the obtained electro-deposited coated steel sheet, as a coating for a sagging resistance test.

[0150] [Preparation of coated panels for sag resistance test]

[0151] The water-based coloring coating composition No. 1 to No. 24 was filled in "X JET" (trade name, manufactured by SSI JAPAN, high viscosity micro-piezoelectric jet dispenser, discharge port diameter 100 μm). Then, under the conditions of frequency 350 Hz, supply pressure 0.03 MPa, and a distance of 10 mm between the discharge port and the coated object, at 27° C. and relative humidity 50%, the above-mentioned coating for the sag resistance test was coated with a film thickness gradient in a manner such that a film thickness of approximately 10 μm to 40 μm was obtained in the longitudinal direction. The coated plate was stood up approximately vertically, left for 3 minutes, and then preheated at 80° C. for 3 minutes. Then, after leaving for 7 minutes, it was heated at 140° C. for 30 minutes to cure the coating film, thereby preparing a coated plate for the sag resistance test.

[0152] For the obtained coated plate for the sag resistance test, the film thickness [sag limit film thickness (μm)] at the position of the punching hole with the thinnest film thickness was measured among the punching holes where the coating film sags more than 5 mm from the lower end of the punching hole, and the evaluation was performed. The larger the sag limit film thickness, the better the sag resistance. ◎ and ○ are qualified. The evaluation results are shown in Table 1.

[0153] ◎: The sagging limit film thickness is 20 μm or more.

[0154] ○: The sagging limit film thickness is 15 μm or more and less than 20 μm. △: The sagging limit film thickness is 10 μm or more and less than 15 μm. ×: The sagging limit film thickness is less than 10 μm.

[0155] [Table 1]

[0156]

[0157] [Table 2]

[0158]

[0159] (Note 1) "UH-756VF": trade name, manufactured by ADEKA Corporation, urethane-associated viscosity modifier, solid content concentration 32%,

[0160] (Note 2) "UH-752": trade name, manufactured by ADEKA Corporation, urethane-associated viscosity modifier, solid content concentration 28%,

[0161] (Note 3) “Rheocrysta I-2SX”: trade name, manufactured by Daiichi Kogyo Seiyaku Co., Ltd., cellulose nanofiber, viscosity adjuster, solid content concentration 2%.

[0162] [Preparation of Clear Coating Composition (Z-1)]

[0163] [Production Example 9]

[0164] 233 parts (70 parts solid content) of the acrylic resin emulsion (A2) obtained in Production Example 2 and 78.9 parts (30 parts solid content) of "Bayhydur VPLS2310" (trade name, manufactured by Sumika Bayer Urethane Co., Ltd., blocked polyisocyanate compound, solid content concentration 38%) were uniformly mixed in a stirring mixing container, and deionized water was added and stirred so that the coating solid content concentration became 40%, thereby obtaining a one-component water-based clear coating composition (Z-1).

[0165] [Preparation of coated material for distinctness of image test]

[0166] [Preparation of Coated Material (O-1) for Image Visibility Test]

[0167] The surface of a black polypropylene plate of 100 mm in length × 100 mm in width × 2 mm in thickness was wiped with gauze containing petroleum benzine for degreasing treatment, and then "ASCREX #2850" (trade name, manufactured by Kansai Paint Co., Ltd., a polyolefin-containing water-based primer coating) was applied with a manual spray gun so that the cured coating film became 15 μm. After leaving it for 5 minutes, it was preheated at 80° C. for 3 minutes to prepare a coated article for a distinctness of image test (O-1).

[0168] [Preparation of Coated Material for Image Diffusivity Test (O-2)]

[0169] On the alloyed hot-dip galvanized steel sheet treated with zinc phosphate, "ELECRON9400 HB" (trade name: manufactured by Kansai Paint Co., Ltd., obtained by using a blocked polyisocyanate compound as a curing agent in an amine-modified epoxy resin-based cationic resin) was electrodeposited to a film thickness of 20 μm, and heated at 170°C for 30 minutes to cure it to form an electrodeposited coating film. Next, "WP-522H" (trade name, manufactured by Kansai Paint Co., Ltd., polyester resin-based water-based mid-coat paint) was applied to the electrodeposited coating film using a manual spray gun to a cured coating film of 15 μm, and after leaving it for 5 minutes, it was preheated at 80°C for 3 minutes to prepare a coating for a distinctness of image test (O-2).

[0170] [Preparation of Coated Material for Image Visibility Test (O-3)]

[0171] The surface of a black polypropylene plate of 100 mm in length × 100 mm in width × 2 mm in thickness was wiped with gauze containing petroleum ether for degreasing, and then "ASCREX#2850" (trade name, manufactured by Kansai Paint Co., Ltd., water-based primer containing polyolefin) was applied using a manual spray gun in such a manner that the cured coating film became 15 μm, and after standing for 5 minutes, it was preheated at 80°C for 3 minutes to form an uncured primer coating film. "Retan WB Eco EV base" (manufactured by Kansai Paint Co., Ltd., trade name, water-based coloring primer) was applied on the uncured primer coating film in such a manner that the dry film thickness became 15 μm, and after standing at room temperature for 5 minutes, it was preheated at 80°C for 3 minutes to form an uncured primer coating film. Next, the clear coating composition (Z-1) obtained in Production Example 9 was applied on the uncured base coating film using a manual spray gun so that the cured film thickness became 35 μm, and after leaving it for 7 minutes, it was heated at 120° C. for 30 minutes to cure the base coating film and the clear coating film, thereby preparing a coated object (O-3) for a distinctness of image test.

[0172] [Preparation of Coated Material (O-4) for Image Visibility Test]

[0173] The surface of a black polypropylene plate of 100 mm in length × 100 mm in width × 2 mm in thickness was wiped with gauze containing petroleum ether for degreasing treatment, and then "ASCREX #2850" (trade name, manufactured by Kansai Paint Co., Ltd., water-based primer containing polyolefin) was applied with a manual spray gun in such a manner that the cured coating film became 15 μm, and after being left for 5 minutes, it was preheated at 80°C for 3 minutes to form an uncured primer coating film. "Retan WB Eco EV base" (manufactured by Kansai Paint Co., Ltd., trade name, water-based coloring primer) was applied on the uncured primer coating film in such a manner that the dry film thickness became 15 μm, and after being left at room temperature for 5 minutes, it was preheated at 80°C for 3 minutes to form an uncured primer coating film. Next, "Retan WB Eco EV Clear" (trade name, two-component water-based clear coating, manufactured by Kansai Paint Co., Ltd.) was applied on the uncured base coating film using a manual spray gun so that the cured film thickness became 35 μm, and after leaving it for 7 minutes, it was heated at 80° C. for 30 minutes to cure the base coating film and the clear coating film, thereby preparing a coated article for a distinctness of image test (O-4).

[0174] [Preparation of Coated Material for Image Visibility Test (O-5)]

[0175] On the alloyed hot-dip galvanized steel sheet treated with zinc phosphate, "ELECRON9400 HB" (trade name: manufactured by Kansai Paint Co., Ltd., obtained by using a blocked polyisocyanate compound as a curing agent in an amine-modified epoxy resin-based cationic resin) was electro-deposited to a film thickness of 20 μm, and heated at 170°C for 30 minutes to cure it to form an electrodeposited coating film. Next, "WP-522H" (manufactured by Kansai Paint Co., Ltd., trade name, polyester resin-based water-based mid-coat paint) was applied on the electrodeposited coating film with a manual spray gun to a cured coating film thickness of 15 μm, and after leaving it for 5 minutes, it was preheated at 80°C for 3 minutes to form an uncured mid-coat coating film. "Retan WB Eco EV base" (manufactured by Kansai Paint Co., Ltd., trade name, water-based pigmented base coating) was applied to the uncured intermediate coating film so that the dry film thickness became 15 μm, and after being left at room temperature for 5 minutes, it was preheated at 80° C. for 3 minutes to form an uncured base coating film. Next, "Retan WB Eco EV Clear" (manufactured by Kansai Paint Co., Ltd., trade name, two-component water-based clear coating) was applied to the uncured base coating film with a manual spray gun so that the cured film thickness became 35 μm, and after being left for 7 minutes, it was heated at 80° C. for 30 minutes to cure the base coating film and the clear coating film, thereby preparing a coated article for a distinctness of image test (O-5).

[0176] [Example 21]

[0177] [Preparation of coated panels for image clarity tests]

[0178] [Preparation of coated plate for distinctness of image test (S1)]

[0179] The water-based colored coating composition No. 1 was filled in "X JET" (trade name, manufactured by SSI JAPAN Co., Ltd., high viscosity micro-piezoelectric jet dispenser, discharge port diameter 100 μm), and applied to the substrate for image clarity test (O-1) so that the dry film thickness was 10 μm under the conditions of frequency 350 Hz, supply pressure 0.03 MPa, distance between the discharge port and the substrate 10 mm, 27° C., and relative humidity 50% to form an uncured colored coating film after being left at room temperature for 5 minutes and then preheated at 80° C. for 3 minutes. Subsequently, the clear coating composition (Z-1) obtained in Production Example 9 was applied to the uncured colored coating film with a manual spray gun so that the cured film thickness was 35 μm, and after being left for 7 minutes, the colored coating film and the clear coating film were cured by heating at 120° C. for 30 minutes to prepare a coated plate for image clarity test (S1-1).

[0180] [Preparation of coated plate for image clarity test (S2)]

[0181] A coated plate for a distinct image test (S2-1) was prepared in the same manner as in [Preparation of a coated plate for a distinct image test (S1)] except that the coated plate for a distinct image test (O-1) was changed to the coated plate for a distinct image test (O-2).

[0182] [Preparation of coated plate for distinctness of image test (S3)]

[0183] A coated plate for a distinct image test (S3-1) was prepared in the same manner as in [Preparation of a coated plate for a distinct image test (S1)] except that the coated plate for a distinct image test (O-1) was changed to the coated plate for a distinct image test (O-3).

[0184] [Preparation of coated plate for distinctness of image test (S4)]

[0185] The water-based color coating composition No. 1 was filled in "X JET" (trade name, manufactured by SSI JAPAN, high viscosity micro-amount piezoelectric jet dispenser, discharge port diameter 100 μm), and applied to the coating material for the image clarity test (O-4) so ​​that the dry film thickness was 10 μm under the conditions of frequency 350 Hz, supply pressure 0.03 MPa, distance between the discharge port and the coating material 10 mm, 27° C., and relative humidity 50% to form an uncured color coating film after being left at room temperature for 5 minutes and then preheated at 80° C. for 3 minutes. Then, "Retan WB Eco EV Clear" (manufactured by Kansai Paint Co., Ltd., trade name, two-component water-based clear coating) (Z-2) was applied to the uncured color coating film with a manual spray gun so that the cured film thickness was 35 μm, left for 7 minutes, and then heated at 120° C. for 30 minutes to cure the color coating film and the clear coating film, thereby preparing a coated plate for the image clarity test (S4-1).

[0186] [Preparation of coated plate for distinctness of image test (S5)]

[0187] A coated plate for a distinct image test (S5-1) was prepared in the same manner as in [Preparation of a coated plate for a distinct image test (S4)] except that the coated plate for a distinct image test (O-4) was changed to the coated plate for a distinct image test (O-5).

[0188] [Examples 22 to 44 and Comparative Examples 5 to 8]

[0189] Except that the combination of the aqueous coloring coating composition and the film thickness in Example 21 was set as the combination shown in Table 2, coated plates for distinctness of image test (S1-2) to (S1-28), (S2-2) to (S2-28), (S3-2) to (S3-28), (S4-2) to (S4-28), and (S5-2) to (S5-28) were prepared in the same manner as in Example 21.

[0190] [Brightness of image test]

[0191] Based on the Short Wave (SW) value measured by "Wave Scan" (trade name, manufactured by BYK Gardner), the distinctness of image was evaluated for the coated plates for distinctness of image test obtained in Examples 21 to 44 and Comparative Examples 5 to 8. The smaller the SW value, the higher the distinctness of image of the coated surface, and ◎ and ○ are acceptable. The evaluation results are shown in Table 2.

[0192] ◎: Sw value is less than 25.

[0193] ○: Sw value is 25 or more and less than 30.

[0194] △: Sw value is 30 or more and less than 40. ×: Sw value is 40 or more.

[0195] [Table 3]

[0196]

Claims

1. An aqueous colored coating composition is applied using a liquid discharge head that controls discharge by changing the relative distance between a valve body and a discharge port. The aqueous colored coating composition has a temperature of 23° C. and a shear rate of 1,000 sec. -1 The viscosity (V1) is 20-100 mPa·s and the shear rate is 0.1 sec at a temperature of 23°C. -1 The viscosity (V2) is 5,000 to 40,000 mPa·s.

2. The aqueous colored coating composition according to claim 1, wherein The solid content concentration of the aqueous colored coating composition is in the range of 10 to 25% by mass.

3. The aqueous colored coating composition according to claim 1 or 2, wherein The aqueous colored coating composition has a tanδ (loss elastic modulus / storage elastic modulus) in the range of 0.25 to 0.80 at a temperature of 23°C.

4. The aqueous colored coating composition according to any one of claims 1 to 3, wherein At a temperature of 23°C, the shear rate was set to 0.1 sec -1 The viscosity (V3) of the aqueous coloring coating composition after 50 seconds is maintained and the shear rate is changed to 1,000 sec. -1 The viscosity (V4) of the aqueous coloring coating composition after 10 seconds is maintained and the shear rate is changed to 0.1 sec -1 The viscosity (V5) of the aqueous coloring coating composition after 10 seconds satisfies the following formula (1) and formula (2): 0.001 < V4 / V3 < 0.007 Formula (1) 30 < V5 / V4 < 200 Formula (2).

5. The aqueous colored coating composition according to any one of claims 1 to 4, wherein The aqueous colored coating composition contains an acrylic resin emulsion (A) and a viscosity modifier (B).

6. A method for forming a multilayer coating film, comprising: Step 1: Using a liquid discharge head that controls discharge by changing the relative distance between a valve body and a discharge port, discharging the aqueous colored coating composition according to any one of claims 1 to 5 adjacent to an object to be coated, thereby forming a colored coating film on the object to be coated; Step 2: Coating a transparent coating composition on the colored coating film to form a transparent coating film.

7. The method for forming a multilayer coating film according to claim 6, wherein: The dry film thickness of the colored coating film is in the range of 1.0 to 15.0 μm.

Citation Information

Patent Citations

  • Coating compositions and systems and methods of applying such coating compositions

    WO2020232011A1